Relationships of sensory processing sensitivity with creativity and empathy in an adult sample - Laros-van Gorkom, Britta A. P.; Damatac, Christienne G.; Stevelmans, Inez; Greven, Corina U. (Frontiers in Psychology, 2025)
Sensory Processing Sensitivity (SPS) describes individual differences in sensitivity to environments, but there is little research on potential positive correlates of SPS. Hereby we investigate whether SPS and its Aesthetic Sensitivity (AES) component are associated with different facets of creativity and empathy. Questionnaires on SPS, creativity and empathy were administered to 296 participants and data were analyzed using hierarchical multiple regression. Higher SPS total and AES scores were associated with more creative ideas (SPS: β=.294304, pfdr<.001=2.00x10-07; AES: β=.49843, pfdr=4.00×10 -16 <.001). Only AES was associated with more creative activities (AES: β=.2924, pfdr<.001=2.48x10 -07 ). Furthermore, higher SPS total and AES scores were associated with more overall empathy (SPS: β=.4298, pfdr=1.84x10 -14 <.001; AES: β=.3753, pfdr=3.91x10 -11 <.001), affective empathy (SPS: β=.5057, pfdr<.001=6.00x10 -16 ; AES: β=.331, pfdr<.001=1.14x10 -08 ) , cognitive empathy (SPS: β=.27692, pfdr<.001=3.60x10 -06 ; AES: β=.35470, pfdr<.001=2.52x10 -09 ), and less emotional disconnection (SPS: β=.2374, pfdr=<.0014.40x10 -05 ; AES: β=.2120, pfdr=<.001.0003). Most associations remained significant after controlling for openness to experience, and the other SPS components of ease of excitation and low sensory threshold heeft opmaak toegepast: Engels (Verenigde Staten)